Insights from European nations on the spatial impacts of renewable energy sources on CO2 emissions - Jing-he Wang; Jamal Mamkhezri; Mohsen Khezri; Mohammad Sharif Karimi; Yousaf Ali Khan (Energy Reports, 2022)
Previous studies ignore the geospatial dynamics effects between renewable energy (RE) and CO2 while assessing such impacts in European countries. Further, most studies wrongfully use RE in its aggregated format rather than decomposing RE by its components. This is important as not all the RE sources share the same characteristics. We fill these gaps in the literature by investigating the effects of various forms of RE on CO2 emissions in 36 European countries from 2000 to 2018. Spatial econometric models have been used to better understand the results. A series of indicative tests confirmed the use of the Durbin panel model and the inclusion of spatial interaction of CO2 emissions in models. Our results confirm the Environmental Kuznets Curve hypothesis in our sample. We identify a positive and significant effect of economic growth (captured through GDP per capita), foreign direct investment, urbanization, and energy intensity on CO2 emissions. Our findings indicate that increasing well-established RE technologies such as geothermal and hydropower lower CO2 emissions. However, increasing RE sources with more advanced technologies such as solar, wind, and bioenergy either increase or have no impact on CO2 emissions. Increasing RE sources as a whole result in a reduction of CO2 emissions in our sample of countries. Moreover, our spatial models suggest that foreign direct investment lowers local CO2 emissions, while neighboring countries’ energy intensity and trade openness increase local CO2 emissions. Lastly, we find solar and bioenergy generation in adjacent countries increase local CO2 emissions, whilst geothermal generation in adjacent countries lowers local CO2 marginally.